2019
DOI: 10.2196/15620
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Inpatient Aggression in Forensic Services Using Remote Monitoring Technology: Qualitative Study of Staff Perspectives

Abstract: BackgroundMonitoring risk of imminent aggression in inpatient forensic mental health services could be supported by passive remote monitoring technology, but staff attitudes toward the relevance and likelihood of engagement with this technology are unknown.ObjectiveThis study aimed to explore staff views, specifically potential benefits and implementation barriers, on using this technology for monitoring risk of inpatient aggression.MethodsWe conducted semistructured focus groups with nurses in an inpatient fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The multilevel models used by Looff et al (2019) showed that HR and SC levels rose significantly in the 20-minute period immediately preceding aggressive behavior. This may potentially provide further opportunities to both design and implement interventions that precede imminent aggressive and violent behavior, which are either aimed at cueing staff members of imminent aggression (Goodwin et al, 2019;Greer et al, 2019) or providing a person displaying AB with real-time information of the bodily signals that precede aggressive behavior (Derks et al, 2019). Overall, based on the current results, it is worthwhile to explore unobtrusive ANS measures as additional risk assessment tools.…”
Section: Discussionmentioning
confidence: 88%
“…The multilevel models used by Looff et al (2019) showed that HR and SC levels rose significantly in the 20-minute period immediately preceding aggressive behavior. This may potentially provide further opportunities to both design and implement interventions that precede imminent aggressive and violent behavior, which are either aimed at cueing staff members of imminent aggression (Goodwin et al, 2019;Greer et al, 2019) or providing a person displaying AB with real-time information of the bodily signals that precede aggressive behavior (Derks et al, 2019). Overall, based on the current results, it is worthwhile to explore unobtrusive ANS measures as additional risk assessment tools.…”
Section: Discussionmentioning
confidence: 88%
“…All study documents were related to mental health research and consisted of a variety of study types and fields, such as clinical trials, cross-sectional investigations and qualitative studies (e.g. Martland et al, 16 Greer at al 17 ). This was supplemented by a detailed qualitative analysis of patient/carer FAST-R member reviews found on the feedback forms and on the documents themselves.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, some of the included studies raised ethical objections related to the use of these security measures (Nolan & Volavka, 2006; Stolovy et al, 2015; Tully et al, 2015), according to literature (Appenzeller et al, 2020). Moreover, the implementation of some technologies could lead to concerns about the violation of privacy or limitation of freedom (Greer et al, 2019; Morris, 2021; Simpson, 2022) and the legal system of some countries may not allow their use in healthcare. Furthermore, the cost of introducing some measures, as in the case of PAs which cost $160.000 (Emmerson et al, 2007), may not be affordable in all countries or hospitals.…”
Section: Discussionmentioning
confidence: 99%